ESTUDO DOS FATORES ASSOCIATIVOS DOS ESTILOS DE APRENDIZAGEM DOS ACADÊMICOS DO CURSO DE CIÊNCIAS CONTÁBEIS - Cleston Alexandre dos Santos; Laurindo Panucci Filho; Nelson Hein (Revista Gestão Universitária na América Latina, 2018)
Learning styles hold approaches related to each person’s characteristics. In the educational field, it is necessary that each teacher develop a teaching plan that allows him to work and interact in a dynamic way with the different learning styles of his students. The present study aims at demonstrating the associative factors related to the learning styles of students enrolled in the Accounting course at the Regional University of Blumenau (FURB), Brazil. As regards the method, this is a descriptive, statistical, cross-sectional study. It can be considered formal, ex post facto and field survey. Data was collected by means of a questionnaire and data collection took place in the months of May and June/2015. As participants, 151 of the 271 enrolled in the course took part in the study. Results revealed that the converging learning style prevailed among the participants. With the aid of correspondence analysis conducted with the software LHStat®, the perceptual map suggested the association of the accommodating and diverging learning styles with the students in the beginning of the course, with the female gender, with students of up to 20 years old and with the students who dedicate many hours of their week to study. As well, results indicated the association of the assimilating and converging learning styles with the students in the final stage of the course, with the male gender, with ages between 21 to 25 years old and with the ones who have a relevant number of hours available to study a week.